Antistatic TPE (thermoplastic elastomer) material as well as preparation method and application thereof
By rationally preparing anticidering TPE materials in TPE materials, including hydrogenated styrene elastomes, mineral oil, ABS, thermoplastic polyurethane, styrenea -lisa acidic anhydride cluster and polyether, polyamide, solved the existing technology After adding anti -static agents, the TPE material cannot cover ABS, and realizes the improvement of good glue, antistatic and mechanical strength of ABS materials.
Patent Information
- Application Number
- CN202411536188.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-31
AI Technical Summary
In the prior art, the TPE material used to encapsulate ABS will affect hydrogen bonds in polar groups in the material after adding antistatic agent, resulting in the inability to effectively coat ABS.
An antistatic TPE material is used, which consists of hydrogenated styrene elastomer, mineral oil, ABS, thermoplastic polyurethane, styrene maleic anhydride copolymer and polyether block polyamide, through specific proportions and processing techniques , improve the coating performance and mechanical strength of the material.
It has achieved good encapsulation, antistatic properties and mechanical strength improvement of ABS material, and can be effectively used for encapsulation of TPE to improve the touch feel and grip of the product.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to an antistatic TPE material and a preparation method and application thereof. Background Art
[0002] Acrylonitrile-butadiene-styrene plastic (ABS) resin is a widely used polymer. It organically unifies the various properties of BS, SAN, and PS. BS improves its toughness, impact and cold resistance; SAN gives ABS resin chemical stability, oil resistance, certain rigidity and hardness; PS gives it good dielectric properties and good processability. It is found in actual use that ABS products made of ABS rubber have stable dimensions, excellent mechanical properties with a balance of toughness, hardness and rigidity, and excellent low-temperature impact resistance. Therefore, ABS is often used to make the gripping part of tools.
[0003] Thermoplastic elastomer (TPE for short) is a polymer composite material that has both the processing properties of thermoplastics and the physical properties of vulcanized rubber. The product has the high elasticity, high strength, and high resilience of rubber, as well as the characteristics of convenient processing and wide processing methods of ordinary plastics. An important application of TPE is coating materials (encapsulation), which is to encapsulate TPE soft rubber materials on other materials. Because TPE materials have good anti-slip properties and good elastic touch, they can improve the touch feel of products and enhance the grip. TPE soft rubber can be adjusted to the appropriate hardness (hardness range Shore 25-90A) and appropriate physical properties (such as wear resistance and scratch resistance, adhesion, melt index, etc.) according to the physical property requirements of the product, providing various possible material application solutions for different products. TPE is processed by encapsulation injection bonding, and commonly used products include handles, grips, electronic materials, etc. TPE materials give products a comfortable touch, improve grip, enhance product aesthetics and product added value. TPE rubber is bonded to some commonly used general plastics PP, GPPS, HIPS, ABS and engineering plastics such as PC, PC / ABS, PA, POM and their modified materials.
[0004] However, in the prior art, the TPE material used for encapsulating ABS has the following main defects: after the antistatic agent is added to the TPE material, it will greatly affect the hydrogen bonds in the polar groups in the TPE material, resulting in the inability to encapsulate ABS. Summary of the invention
[0005] The purpose of the present invention is to overcome the above technical defects and provide a TPE material with good ABS encapsulation, antistatic and high mechanical strength, and a preparation method and application thereof.
[0006] The present invention is achieved through the following technical solutions: An antistatic TPE material comprises the following components in parts by weight: 9-31 parts of hydrogenated styrene elastomer; Mineral oil 19-61 parts; ABS 0.5-9 parts; Thermoplastic polyurethane 4-16 parts; 1-21 parts of styrene maleic anhydride copolymer; Polyether block polyamide 4-16 parts.
[0007] As an example, the hydrogenated styrene elastomer content can be 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts.
[0008] As an example, the mineral oil content can be 19 parts, 21 parts, 23 parts, 25 parts, 27 parts, 29 parts, 31 parts, 33 parts, 35 parts, 37 parts, 39 parts, 41 parts, 43 parts, 45 parts, 47 parts, 49 parts, 51 parts, 53 parts, 55 parts, 57 parts, 59 parts, and 61 parts.
[0009] As an example, the ABS content may be 0.5 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, or 9 parts.
[0010] As an example, the thermoplastic polyurethane content can be 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts.
[0011] As an example, the content of styrene maleic anhydride copolymer can be 1 part, 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts, 19 parts, and 21 parts.
[0012] As an example, the polyether block polyamide content can be 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts.
[0013] The hydrogenated styrene elastomer is selected from at least one of hydrogenated styrene-butadiene block copolymer and hydrogenated styrene-isoprene block copolymer.
[0014] The present invention has no special requirements for the parameters of ABS. As an example, the MFR (230° C. / 2.16 kg) of ABS may be 1.2-20 g / 10 min.
[0015] The mineral oil is selected from at least one of white oil, paraffin oil, cycloparaffin oil and aromatic hydrocarbon oil.
[0016] The thermoplastic polyurethane is selected from at least one of polyester polyurethane and polyether polyurethane.
[0017] Polyester polyurethane is composed of monomers of 4,4'-diphenylmethane diisocyanate (MDI), 1,4-butanediol (BDO), and adipic acid (AA), wherein the content of MDI is about 35-45 wt%, AA is about 30-40 wt%, and BDO is about 20-30 wt%.
[0018] Polyether polyurethane: The main monomers are 4,4'-diphenylmethane diisocyanate (MDI), polytetramethylene glycol (PTMEG), and 1,4-butanediol (BDO), of which the content of MDI is about 35-45 wt%, PTMEG is about 35-45 wt%, and BDO is about 15-25 wt%.
[0019] The styrene maleic anhydride copolymer is selected from at least one of styrene maleic anhydride N-phenylmaleimide terpolymer and styrene-maleic anhydride copolymer.
[0020] Specifically, the styrene maleic anhydride N-phenylmaleimide terpolymer is a terpolymer composed of a styrene monomer, a maleic anhydride monomer, and an N-phenylmaleimide monomer, and may be a random copolymer or a block copolymer.
[0021] Styrene-maleic anhydride copolymer is a copolymer of styrene monomer and maleic anhydride monomer, and may be a random copolymer or a block copolymer.
[0022] The maleic anhydride content in the styrene maleic anhydride copolymer that can achieve the purpose of the present invention can be in the range of 8-45wt%. Preferably, the maleic anhydride content in the styrene maleic anhydride copolymer is in the range of 12-35wt%. More preferably, the maleic anhydride content in the styrene maleic anhydride copolymer is in the range of 18-25wt%.
[0023] Test method for maleic anhydride content: titration method is adopted, and sodium hydroxide (NaOH) is used as titrant. NaOH reacts with maleic anhydride to generate water-soluble sodium salt. During titration, the maleic anhydride sample is dissolved in an appropriate solvent, and an indicator (such as phenolphthalein) in a methanol solution is added. The end point of the color change of the titrant is observed by titrating the NaOH solution in the solution, thereby determining the content of maleic anhydride.
[0024] The weight average molecular weight of the styrene maleic anhydride copolymer is in the range of 3000-150000, and the weight average molecular weight is measured by gel permeation chromatography.
[0025] Polyether block polyamide is composed of regular linear hard polyamide segments embedded in soft polyether segments.
[0026] Other components can be added according to actual needs, and 0-2 parts of auxiliary agents are also included by weight, and the auxiliary agents are selected from at least one of antioxidants, lubricants, and light stabilizers. The antioxidant can be one or more of 2,6-di-tert-butyl-4-methylphenol, antioxidant 1010, antioxidant 1076, antioxidant 1790, antioxidant 168, or antioxidant 626. The light stabilizer can be a mixture of hindered amine light stabilizers and triazine light stabilizers in a weight ratio of 2:1. The hindered amine light stabilizer can be one or more of light stabilizer 622, light stabilizer 770, light stabilizer 944, light stabilizer 783, light stabilizer 791, light stabilizer 3853, light stabilizer 292, or light stabilizer 123; the triazine light stabilizer is one or more of UV-234, UV-236, or UV-2373. The lubricant is one or more of vinyl bisstearamide, hydroxy fatty acid lubricant, erucic acid amide, zinc stearate, magnesium stearate or polyethylene wax.
[0027] It is also possible to choose whether to add 0-50 parts of filler according to actual conditions. The filler may be white carbon black, wollastonite, calcium carbonate, glass microbeads, talcum powder, kaolin, diatomaceous earth, barium sulfate, mica, etc.
[0028] The preparation method of the antistatic TPE material of the present invention comprises the following steps: firstly spraying mineral oil on hydrogenated styrene elastomer to prepare solid one-step material, then uniformly mixing with other components, and extruding and granulating through a twin-screw extruder, wherein the screw temperature range is 170-250° C., to obtain the antistatic TPE material.
[0029] The antistatic TPE material of the present invention is used for encapsulating ABS.
[0030] The tensile strength of the antistatic TPE material of the present invention is ≥2MPa, and the surface resistivity is greater than e*10 4 Less than e*10 11 Ohm, bonding strength> 2 N / mm and reaches grade C and D.
[0031] The present invention has the following beneficial effects: The carbamate group in the thermoplastic polyurethane has a high strength, which can greatly improve the strength and toughness of the material. At the same time, due to its high polarity, it has a high compatibility with ABS, which can greatly improve the encapsulation performance of the material. At the same time, the addition of styrene maleic anhydride copolymers, on the one hand, promotes the compatibility of the three components of polyether block polyamide, hydrogenated styrene elastomer, and ABS to improve the overall material strength, establish better ion channels to improve material compatibility, and on the other hand, can improve the activity of carbamate construction and promote the bonding of the substrate to ABS. The ABS material of the present invention not only has the advantages of high antistatic properties and mechanical strength, but also has excellent compatibility with TPE materials, and can be used for encapsulating TPE. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0033] The sources of raw materials used in the present invention are as follows: A: hydrogenated styrene-butadiene block copolymer, SEBS 7551, Lee Chang-jung, Taiwan, China; B: cycloparaffin oil, 500N, China Nanlian; C: ABS, Bayblend 2253, Bayer, Germany; D1: polyester polyurethane, Desmopan 365X from Covestro; D2: polyether polyurethane, Desmopan DP6065A from Covestro; E1: styrene maleic anhydride copolymer, maleic anhydride content 23wt%, XIRAN®3500, Polyscope, Netherlands; E2: styrene maleic anhydride copolymer, maleic anhydride content 19wt%, XIRAN®4000, Polyscope, Netherlands; E3: styrene maleic anhydride copolymer, maleic anhydride content 13wt%, XIRAN®6000, Polyscope, Netherlands; E4: styrene maleic anhydride copolymer, maleic anhydride content is 10wt%, XIRAN®9000, Polyscope, Netherlands; E5: styrene maleic anhydride copolymer, maleic anhydride content is 32wt%, XIRAN®2500, Polyscope, Netherlands; E6: styrene maleic anhydride copolymer, maleic anhydride content is 42wt%, XIRAN®1000, Polyscope, Netherlands; E7: styrene maleic anhydride N-phenylmaleimide terpolymer, maleic anhydride content is 10wt%, XIRAN® IZ1018M, Polyscope, Netherlands; F1: polyether block polyamide, Pebax 7033 SP01, Arkema, France; F2: polyether block polyamide, Pebax 5533 SP 01, Arkema, France; F3: quaternary ammonium salt polymer, HDC-100K, Lin'an Dechang; F4: sulfonate polymer, HDC-193K Lin'an Dechang; G: Heavy calcium carbonate, CC903, Cologne powder; J1: antioxidant, Irganox 1010, Irgafos 168, BASF; J2: antioxidant, Irganox 1076 BASF; J3: Light stabilizer, Cyasorb UV-3808pps, Cytec.
[0034] In the embodiment table, J is J1:J2:J3=1:5:5.
[0035] Embodiment and comparative example The preparation method of antistatic ABS material: first spray mineral oil on hydrogenated styrene elastomer to prepare solid one-step material, then mix it with other components evenly, and extrude granulate through a twin-screw extruder. The screw temperature position is 170℃-180℃-200℃-200℃-200℃-200℃-200℃-210℃ to obtain antistatic ABS material.
[0036] Various test methods: (1) Adhesion strength test method: According to the requirements of GB / T 7760-2003 standard, use an injection molding machine to inject the antistatic ABS material to be tested onto the ABS substrate sample on a specific mold, and the injection molding temperature is 235℃. After being placed at room temperature for 24 hours, 90° peeling is performed to test the bonding strength between TPE and ABS substrate sample. Note: For the adhesion strength test, A: It can be easily peeled off, and the peeling surface is smooth and has no residue. B: The peeling force is large, and the peeling surface residue is as high as 50%. C: It is difficult to peel off the edges and corners, the residue is 50%-99%, and the peeling force is large. D: It is difficult to peel off the edges and corners, and the TPE is broken. The higher the adhesion strength value, the better, and the above test results meet the requirements when they reach level C or level D.
[0037] (2) Tensile strength test method: According to ISO527-2012 standard test, after injection molding into a 2*100*100mm standard square plate, use a cutter to cut into 2-type specimens, place at room temperature for 24 hours, and then test on a tensile machine. The molding cycle shall be based on the cycle of the injection molding tensile specimen.
[0038] (3) Surface resistivity test method: After the sample is injection molded into a 2*100*100mm standard square plate, it is placed at room temperature for 24 hours and then its surface resistivity is tested using a surface resistivity meter. Note: For antistatic materials, the lower the surface resistivity, the better the antistatic performance, and the larger the surface resistivity, the better the insulation performance. The surface resistivity of an object is greater than or equal to e*10 14 Ohm is an insulator. Greater than e*10 4 Less than e*10 11 Ohm is an antistatic material.
[0039] Table 1: Components (parts by weight) and test results of antistatic ABS materials in Examples 1-5 Example 1 Example 2 Example 3 Example 4 Example 5 A 15 25 15 30 25 B 30 25 30 60 25 C 3 3 8 1 3 D1 8 10 12 10 D2 15 E1 1 5 8 20 E2 5 F1 10 10 10 15 15 G 20 20 20 20 J 1.1 1.1 1.1 1.1 1.1 Adhesion strength, N / mm 3.8 4.2 4.8 5.8 3.9 Stripping state D D C D D Tensile strength, MPa 5.1 6.1 7.2 14 6.0 Surface resistivity (Ω) <![CDATA[e*10 8 ]]> <![CDATA[e*10 8 ]]> <![CDATA[e*10 8 ]]> <![CDATA[e*10 7 ]]> <![CDATA[e*10 9 ]]> Table 2: Components (parts by weight) and test results of antistatic ABS materials in Examples 6-11 Example 6 Example 7 Example 8 Example 9 Example 10 Embodiment 11 A 25 25 25 25 25 15 B 25 25 25 25 25 30 C 3 3 3 3 3 3 D1 10 10 10 10 10 8 E1 1 E3 5 E4 5 E5 5 E6 5 E7 5 F1 15 15 15 15 15 F2 10 G 20 20 20 20 20 20 J 1.1 1.1 1.1 1.1 1.1 1.1 Adhesion strength, N / mm 3.4 2.7 3.2 2.1 2.6 3.5 Stripping state C C D D C D Tensile strength, MPa 4.8 4.2 4.1 2.5 4.7 4.6 Surface resistivity (Ω) <![CDATA[e*10 7 ]]> <![CDATA[e*10 8 ]]> <![CDATA[e*10 9 ]]> <![CDATA[e*10 11 ]]> <![CDATA[e*10 11 ]]> <![CDATA[e*10 8 ]]> It can be seen from Examples 2 / 5-10 that when the maleic anhydride content is 18-25wt%, the bonding strength is the highest, the edge peeling is difficult, and the tensile strength is the highest; when the maleic anhydride content is 12-35wt%, the bonding strength is greater than 3.0N / mm, the peeling test reaches C / D level, and the tensile strength is greater than 4MPa.
[0040] Table 4: Components (parts by weight) and test results of antistatic ABS materials in comparative examples 1-3 Comparative Example 1 Comparative Example 2 Comparative Example 3 A 15 15 15 B 30 30 30 C 3 3 3 D1 1.5 8 8 E1 1 0 35 F1 10 10 10 G 20 20 20 J 1.1 1.1 1.1 Adhesion strength, N / mm 2.2 0.2 1.4 Stripping state B A D Tensile strength, MPa 3.4 2.3 4.1 Surface resistivity (Ω) <![CDATA[e*10 10 ]]> <![CDATA[>e*10 12 ]]> <![CDATA[e*10 8 ]]> It can be seen from Comparative Example 1 that when the content of thermoplastic polyurethane is too low, the bonding strength is low.
[0041] It can be seen from Comparative Example 2 that if the styrene maleic anhydride copolymer is not contained, the bonding strength is extremely poor, and the dispersion of the polyether block polyamide is poor, resulting in an excessively large surface resistivity and poor antistatic performance.
[0042] It can be seen from Comparative Example 3 that due to the excessively high content of styrene maleic anhydride copolymer, the tensile strength of the ABS material in Comparative Example 3 is low, resulting in a small force value when breaking. Although it reaches D, it has no practical value.
[0043] Table 5: Components (parts by weight) and test results of antistatic ABS materials in comparative examples 4-7 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 A 15 15 25 25 B 30 30 25 25 C 0 18 3 3 D1 8 8 10 10 E1 1 1 5 5 F1 10 10 F3 10 F4 10 G 20 20 20 20 J 1.1 1.1 1.1 1.1 Adhesion strength, N / mm 1.1 3.7 1.7 0.9 Stripping state A B A A Tensile strength, MPa 3.3 6.0 3.5 5.1 Surface resistivity (Ω) <![CDATA[e*10 8 ]]> <![CDATA[e*10 8 ]]> <![CDATA[e*10 10 ]]> <![CDATA[e*10 8 ]]> It can be seen from Comparative Example 4 that if ABS is not contained, the adhesive strength is low and the tensile strength is not high.
[0044] It can be seen from Comparative Example 5 that if the ABS content is too high, the adhesion only reaches Class B, which does not meet the requirements.
[0045] It can be seen from Comparative Examples 6 / 7 that the technical effect of the present invention cannot be achieved by using the quaternary ammonium salt polymer and sulfonate polymer antistatic agents commonly used in the art.
Claims
1. An antistatic TPE material, characterized in that: By weight, it includes the following components: 9-31 parts of hydrogenated styrene elastomer; Mineral oil 19-61 parts; ABS 0.5-9 parts; Thermoplastic polyurethane 4-16 parts; 1-21 parts of styrene maleic anhydride copolymer; Polyether block polyamide 4-16 parts.
2. The antistatic TPE material according to claim 1, characterized in that: The hydrogenated styrene elastomer is selected from at least one of hydrogenated styrene-butadiene block copolymer and hydrogenated styrene-isoprene block copolymer.
3. The antistatic TPE material according to claim 1, characterized in that: The mineral oil is selected from at least one of white oil, paraffin oil, cycloparaffin oil and aromatic hydrocarbon oil.
4. The antistatic TPE material according to claim 1, characterized in that: The thermoplastic polyurethane is selected from at least one of polyester polyurethane and polyether polyurethane.
5. The antistatic TPE material according to claim 1, characterized in that: The styrene maleic anhydride copolymer is selected from at least one of styrene maleic anhydride N-phenylmaleimide terpolymer and styrene-maleic anhydride copolymer.
6. The antistatic TPE material according to claim 1, characterized in that: In the styrene maleic anhydride copolymer, the maleic anhydride content ranges from 8 to 45 wt%, preferably from 12 to 35 wt%, and more preferably from 18 to 25 wt%.
7. The antistatic TPE material according to claim 1, characterized in that: By weight, the invention further comprises 0-2 parts of auxiliary agents, wherein the auxiliary agents are selected from at least one of antioxidants, lubricants and light stabilizers; and by weight, the invention further comprises 0-50 parts of fillers.
8. The method for preparing the antistatic TPE material according to any one of claims 1 to 7, characterized in that: The following steps are involved: First, the hydrogenated styrene elastomer is sprayed with mineral oil to prepare a solid one-step material, and then mixed with other components evenly, and extruded into granules through a twin-screw extruder with a screw temperature range of 170-250°C to obtain an antistatic TPE material.
9. Application of the antistatic TPE material according to any one of claims 1 to 7, characterized in that: Used for ABS coating.
Citation Information
Patent Citations
TPE material for encapsulating ABS and preparation process for TPE material
CN106751372A
TPE (thermoplastic elastomer) material for coating ABS (acrylonitrile butadiene styrene) and preparation method thereof
CN116554672A
Nylon rubber-coated TPE (thermoplastic elastomer) composite material as well as preparation method and application thereof
CN118006133A
